Histology and Histochemistry of Prostate Gland in Pig (Sus scrofa domestica) - Sailaja, S. Naga; Purushotham, G.; Kumar, D. Pramod; Raghavender, K. B.P (Indian Journal of Veterinary Anatomy, 2018)
Samples from adult boars were utilized for recording histology and histochemistry of Prostate gland. It consisted of pars compacta and pars disseminata. A thin capsule comprised of collagen, reticular and few elastic fibers with blood vessels covered the compacta. Compacta and disseminata consisted of multiple branched tubuloalveolar secretory segments. The secretory epithelium of compacta were tall cuboidal cells while low columnar to pyramidal cells in disseminata. Ducts were lined by stratified cuboidal cells in compacta whereas stratified columnar cells in disseminata. Concentrically laminated concretions of secretory material (corpora amylacea) were observed in compacta. Propria sub mucosa comprised of loose connective tissue with collagen,reticular fibers and few smooth muscle cells. The muscularis layer was thin and circularly arranged. These muscle fibers extended into the folds of mucosa. Inter and intralobular connective tissue was abundant in disseminata than in compacta.